STRATEGI PENINGKATAN MUTU PESERTA DIDIK MELALUI LAYANAN KONSELING - Elvia Baby Shahbana Hartono (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2019)
School counseling services have a very important role in order to improve the quality of school students to understand about themselves and also recognize their potential. This research was conducted at SD Plus Al-Kautsar Malang using qualitative approach with qualitative descriptive research and a total quality management analysis technique, Flow Chart. Data collection using observation, interviews and documentation. Sources of data obtained from the Principal, Head of Student Affairs and guidance and counseling teachers (BK). The results showed that the improvement in the quality of counseling services was done by increasing the number of counseling staff in schools and then conducted special training for guidance and counseling (BK) teachers because the number of students ranged from more than 500 people so counseling counselors needed approximately 3 counselors, ideally the ratio of guidance and counseling teachers for 1 teacher serving approximately 100-150 students only. School counseling services are considered beneficial for students and parents, because they provide additional support for students in the academic, personal and social fields and careers to improve student achievement. Likewise, parents can collaborate with school counselors to find out problems and forms of problem solving both in the field of learning and potential outside the field of learning. Keywords: counseling Services, total quality management, flow chart